'Valhalla rising': Gender, embodiment and experience in military memoirs. (April 2016) - Dyvik, Synne L
Recent contributions within international relations place embodiment, experience and emotion at the centre of their analysis of war. Recognizing that war should be 'studied up from people and not down from places that sweep blood, tears and laughter away' (Sylvester, 2012: 484), I extend this aim to analyse embodiment and experience through Norwegian military memoirs from Afghanistan. These are relevant empirically not necessarily because they contest political aims or offer policy recommendations, but because of how these embodied narratives, influenced by particular gendered conceptions of 'warrior masculinity' and Viking mythology, can trouble Norwegian public narratives. Through focusing on how memoirs construct the sensory experience of combat, I argue that these enable us to push conceptual understandings of embodiment and experience. Memoirs show how war is experienced as an assemblage of pleasure and pain, and how this is caught up in complex blurrings of individual and collective militarized bodies. Analysing how the pain and pleasure of war is made sense of through and between bodies allows us to advance the usage of embodiment as a concept in international relations, in turn leaving the discipline better equipped to understand war's complex embodied assemblages.